Electrical technology students in vocational colleges: are they healthy mentally? - Lee, M.F.; Sulaiman, K.A.; Lai, C.S. (IOP Publishing, 2020)
Distraction such as depression, anxiety, and stress in mental health problem can influence academic achievement to students, including vocational colleges’ students. Hence, the main purpose of this study was to determine the mental health profiles of Electrical Course students in Vocational Colleges. The difference in mental health level in terms of gender, hometown, and years of study were also be investigated. Besides, the level of mental health elements implementation by teachers in teaching and learning was also determined. This study was employed a survey method as research design that involved of 132 respondents from three vocational colleges in the southern zone. The respondents were selected using strata sampling technique. The instrument of this study was Malay version DASS-21 item inventory. This inventory measures three elements of mental health problem, namely depression, anxiety, and stress through 21 items. Questionnaires for level of mental health elements implementation by teachers in teaching and learning from student perception consists of 21 items. The collected data were analyzed using frequency, percentage, Spearman Rho test, Mann Whitney U test, and Kruskal Wallis test. The findings of this study showed that students' mental health level and the level of mental health elements implementation by teachers in teaching and learning were at the moderate level. The findings also found that there was a significant relationship between each element of mental health with students’ academic achievement level, as well as the level of mental health elements implementation by teachers in teaching and learning. In addition, the results also shows that there were no significant difference in the mental health level among the students from the aspects of gender, hometown, and years of study. In short, an intervention program needs to be implemented to overwhelm students’ mental health problems, because prevention was better than cure.